Reinfeksi Morbus Hansen (MH) serta Penggunaan Methylprednisolone yang Tidak Tepat - wenly susanto (Cermin Dunia Kedokteran, 2024)
Background: Morbus Hansen (MH), or leprosy, is a chronic granulomatous infection caused by Mycobacterium leprae. This disease still has a negative stigma, leading to ostracism. Methylprednisolone use can affect the risk of leprosy re-infection. Case: A 55-year-old female with complaints of abdominal pain, nausea, vomiting, and weakness accompanied by an active leprosy reaction. The patient had a history of leprosy treatment at the Sumenep Health Center in 2000 and at Sumberglagah Leprosy Hospital in 2004, but did not return for an acid-fast bacilli (BTA) check after therapy. She takes methylprednisolone 4 mg once or twice daily to manage an itch or rash. Her dermatological status was a symmetrical leprosy reaction throughout the body, accompanied by erythematous nodules and ulcerated nodules. Smear MH examination results +3 in indirect bacteriology and 25 bacteria in indirect microbiology. Treatment for multibacillary leprosy for 12–18 months and education were planned to increase patient awareness and compliance and appropriate steroid drug use.